(3TQM GdnqfnqXGes
(3ChdgG (B:s
... (3hCeKGdgG hhUaJ GdCUhd HCfgG JYQa HgG CMhGd CHfjI Gdcde djNQL Yf MO GdJUQja GdYde HCUhd ef TCfgG Cf jYQa HgG ZjQ CMhGd GdCHfjI hgj ef GdYdhe eG Shi UfYJj GdEYQGH hGdUQa hNQL HHGbj (B...s
(3BNQgG (B:s
.. (3aEf Lgd MGdg H`Cf de jcf eeG jhLO dg EMOi GdgjFGJ hGdYdGeGJ GdeYOhOI aEf CedjJ aGdjGA fMh eJi hEdG aGdCda (B.. (3cJHh GdPj HGdjGA eY Cfg eLghd GdMGd hdjS dbhdge aj GdEVGaI dOjc acdG jcJH Ydi GdhLgjf(B...(3Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2/216s
(3GdPQjYI (B13\1157s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdUQas